Peningkatan Pengetahuan TPACK dan Media Pembelajaran Berbasis Augmented Reality (AR) Guru MTs PPMI Assalaam - Novi Ratna Dewi; Aji, Septiko; Rizki Nor Amelia; Luthfi Hanum Saputri; Intan Rahmalia; Dita Seplita Sari; Nihayatul Bidayah (Jurnal Dharma Indonesia, 2024)
21st-century learning requires all teachers to implement learning that integrates information and communication technology (ICT). The use of ICT in learning can be realized well if teachers can integrate technology, knowledge, and pedagogical expertise in teaching or what is known as Technological Pedagogical Content Knowledge (TPACK). One way to apply TPACK in learning is to develop Augmented Reality-based learning media. Teachers at MTs PPMI Assalaam have not mastered and applied technology in learning, especially Augmented Reality-based learning media. Based on this situation, the service team felt it was essential to increase TPACK knowledge and prepare Augmented Reality-based learning media through training. The results of the pretest and posttest after training showed an increase, and the participants' response to the service activities through a satisfaction questionnaire was said to be very good.